On an optimal control of the Wiener process - Kolemaev, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Колемаев. Об одной задаче оптимального регулирования винеровского процесса V. Kolemaev. Vinerio proceso optimalaus reguliavimo klausimu